Workers’ Knowledge and Views on Interaction with Health and Safety Representatives: An Exploratory Qualitative Study - Ollé-Espluga, Laia; Vergara-Duarte, Montse; Menéndez-Fuster, María; Benach, Joan; Vázquez, María-Luisa (Relations industrielles / Industrial Relations, 2019)
The action of health and safety representatives (HSRs) has proven beneficial for workers’ occupational health, but a number of determining factors can diminish HSRs’ effectiveness. One understudied factor shaping HSRs’ effectiveness is the interaction that exists between workers and HSRs, that is, the relationship that workers and their representatives establish with each other throughout a wide range of processes.In this paper, we explore the workers’ knowledge and opinions of their interaction with HSRs and its determinants. We undertook a qualitative exploratory and descriptive-interpretative study by means of 22 semi-structured interviews with a theoretical sample of workers from Barcelona and Girona (Spain).Results show a vast unawareness of HSRs’ existence and functions among workers; only the few workers who know the HSRs personally describe interaction processes with them, mainly concerning hazard identification. Some of the workers mentioned processes of interaction with unions regarding health and safety at work. These processes consist mainly in raising issues with union representatives and, in a more limited way, in associating with occupational health mobilizations and participating in decision-making processes. Determining factors of the interaction between workers and -health and safety or union- representatives emerge strongly in relation to representatives and workers and, in a more diluted way, with regard to the context or the firm.The study contributes to the research concerning the building of relations of representativeness as a way to better understand (and represent) workers’ needs and provides strategic insight for collective representation bodies to regain their legitimacy.